Peran Pimpinan Sumber Daya Manusia Menjadi Leader Dalam Penegakan Etika Anti Diskriminatif - Tri Agus Saputra; Chandra Wijaya (PERSPEKTIF, 2022)
This article aims to look at the important role of anti-discriminatory ethics and the role of human resource managers as the main pillars of anti-discriminatory ethics enforcement. Discrimination is one type of ethical problem that arises in the field of employment. The task of eliminating discriminatory actions is generally the responsibility of the state, however, in practice many discriminatory cases that occur are not reached by the state so that in the end it requires an active role from entities outside the state structure to be at the forefront of resolving discriminatory problems. The method used in this study is a qualitative method with a qualitative descriptive approach through literature study. The data obtained and collected from the analysis of documents in the form of books, articles and government regulations. This study concludes that human resource managers are considered the closest and most suitable entity in the realm of ethical management because human resource managers are entities that are very close and face to face with humans in an organization. When talking about ethics, it will be very closely related to the relationship between humans and the relationship between humans and organizations.